Synthesis, Characterization of New Polyamides Bearing Triarylamine for Lightemitting Diodes - hasan, Nehad Tariq; Rashid, Azhar Kamil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this work, new di-acid monomers 4, 4â€™-di-carboxillic-4â€-bromo-2â€, 6â€-dimethyl triphenylamine (Ma), 4, 4â€™- di-carboxylic -4â€-chloro-2â€, 6â€-dimethyl triphenylamine (Mb) and 4, 4â€™- di-carboxylic -2â€,4â€-dichloro-6â€-methyl triphenylamine (Mc) were synthesized by reaction of p-cyanobenzofluride with three different aromatic amines (4-bromo,2,6-dimethyl aniline, 4-chloro,2,6-dimethyl aniline and 2,4 dichloro, 6- methyl aniline )  via aromatic nucleophilc substitution method to form three di cyano intermediates 4, 4â€™-Dicyano-4â€-bromo-2â€, 6â€-dimethyl triphenylamine (Da), 4, 4â€™-dicyano-4â€-chloro-2â€, 6â€-dimethyl triphenylamine (Db) and 4, 4â€™-dicyano-2â€,4â€-dichloro-6â€-methyl triphenylamine (Dc) which form final di-carboxylic monomers after alkaline hydrolysis. Finally, these monomers react with two different aromatic di amines, phenylene diamins and benzidine respectively via polycondensation reaction to form final polyamides 4"-bromo-2", 6"-dimethyl-triphenylamine-4, 4'-polyphenylbenzamide (Pa), 4â€-chloro-2â€,6â€-dimethyl- triphenylamine-4,4'-polyphenylbenzamide (Pb), 2â€,4â€-dichloro-6â€-methyl-triphenylamine 4,4'- polyphenylbenzamide (Pc),4"-bromo-2",6"-dimethyl triphenylamine-4,4'- polyphenylbiphenylamide (Pd), 2â€,4â€-dichloro-6â€-methyl-triphenylamine-4,4â€™-polyphenylamide (Pf).The chemical structure of these polymers characterized by FTIR and NMR techniques. All the results of polyamides showed excellent solubility in most polar solvents to form strong thin films. The polyamides possess a good thermal stability with height glass transition temperatures (Tg).Polyamides in DMSO solvent gave strong photoluminescence PL. Thin casting films of these polyamides in cyclic voltammetry (C.V) on glass base of iridium-tin oxide (ITO) as working electrode in dry CH3CN solvent contains 0.1 M of tetrabutylantimoneperchlorate (TBAP) as anElectrolyte gave one redox wave.